Food categorization determines whether healthier food is inferred to be tastier or less tasty - Mai, Robert; Trendel, Olivier; Basil, Michael (Journal of Consumer Psychology, 2025)
Abstract Despite evidence that people believe that the unhealthier the food, the tastier it is, some studies also suggest the opposing belief—the healthier the food, the tastier it is. A framework is proposed to reconcile this contradiction, and four studies demonstrate that the discrete categorization of foods as healthful versus unhealthful determines which intuition consumers use. When stereotypically unhealthy foods (e.g., candies, ice cream, hot dogs) are encountered, they are automatically categorized as unhealthful and the properties associated with that category (e.g., sweetness, saltiness, fat content) become accessible. Inferences about taste are then based on these properties and the unhealthier the encountered products are (i.e., the higher the sugar and fat content they have), the tastier they are perceived to be (unhealthy = tasty belief). Conversely, when stereotypically healthful foods (e.g., fruits) are encountered, other properties (e.g., freshness, vitamins) become salient, and tastiness is mainly inferred based on these properties, leading to the inference that the healthier these foods are (i.e., the more freshness and vitamins they have), the tastier they are perceived to be (healthy = tasty belief). Marketers and policymakers can leverage these findings to understand better when emphasizing healthiness benefits or hurts taste perceptions.